Aerosol direct effects on global solar shortwave irradiance at high mountainous station Musala, Bulgaria. (1st January 2021) - Nojarov, Peter; Arsov, Todor; Kalapov, Ivo; Angelov, Hristo
Abstract: The aim of this study is to reveal the direct radiative effect of aerosols on global solar shortwave radiation in the region of peak Musala, which has specific climatic and environmental conditions. Correlations between the measured global solar shortwave radiation and the total aerosol content, Ångström exponent in the visible spectrum, absorption of radiation by aerosols, scattering of radiation by aerosols, Single Scattering Albedo (SSA) of aerosols are calculated using statistical methods. The results show that the underlying surface through its albedo plays a significant role in terms of the radiative effect of aerosols. At low albedo values, the higher aerosol amounts exert, at surface level, a negative radiative effect and vice versa. However, at high albedo values, the higher aerosol amounts exert, at surface level, a positive radiative effect and vice versa. This is due to the fact that a higher albedo leads to larger amounts of reflected and scattered shortwave radiation, especially close to the earth's surface, which at higher aerosol amounts result in an increase in the amount of scattered shortwave radiation, which also increases the global solar shortwave radiation. The relationships between global solar shortwave radiation and aerosols are, in most cases, non-linear, which is due to the statistical distributions of the studied parameters, which are not normal. Disclosed dependencies should be taken into account when modeling the impact of aerosols on climate change. Highlights: Surface albedo plays a significant role in terms of radiative effect of aerosols. High albedo leads to a positive radiative effect of aerosols at surface level. Higher albedo causes larger amounts of reflected and scattered shortwave radiation. DRE of aerosols at peak Musala changes its sign at albedo values of about 0.4